2009
DOI: 10.1111/j.1748-7692.2009.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of growth phases for bottlenose dolphins using a Bayesian modeling approach

Abstract: The Gompertz function is the most commonly used growth function for cetacean studies. However, this function cannot represent multiple phases of growth. In this study, we present a Bayesian framework fitting parameters of a triple‐logistic growth function to describe multiple phases of growth for bottlenose dolphins (Tursiops truncatus), simultaneously fitting and comparing all growth parameters between South Carolina (SC), Mississippi Sound (MSS), and Indian River Lagoon (IRL) cohorts. The fitted functions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 19 publications
7
48
1
Order By: Relevance
“…The maximum age recorded in our sample (41 yr) is significantly older than that reported by Glazov & Lyamin (2000) (19 yr) and Karaçam et al (1990) (26 yr), but is similar to the estimates in other regions of the world (McFee et al 2010).…”
Section: Historical Variation and Population Heterogeneitysupporting
confidence: 79%
“…The maximum age recorded in our sample (41 yr) is significantly older than that reported by Glazov & Lyamin (2000) (19 yr) and Karaçam et al (1990) (26 yr), but is similar to the estimates in other regions of the world (McFee et al 2010).…”
Section: Historical Variation and Population Heterogeneitysupporting
confidence: 79%
“…Studies of the age-length relationship on this species in different areas of the western North Atlantic and Gulf of Mexico (Hohn, 1980;Cockcroft and Ross, 1990a;Mead and Potter, 1990;Fernandez and Hohn, 1998;Mattson et al, 2006, McFee et al, 2010 found a remarkable reduction in the growth rates after the fourth year of life. In the present work almost all measurements were still growing in the first two years of life; 91% have stopped at age 4 and only one (ARTPROWD) continued growing after age 5.…”
Section: Discussionmentioning
confidence: 96%
“…bottlenose dolphin total body length has been mathematically described using many different models (e.g. Fernandez and Hohn, 1998;Mattson et al, 2006;Siciliano et al, 2007;McFee et al, 2010), no study has used mathematical equations to model skull growth. From an initial screening of the data it was clear that different measurements exhibited different patterns of growth.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies (i.e. Read et al 1993, Fernandez & Hohn 1998, McFee et al 2010 found mature males to be ~10 cm longer than females. The reason for the absence of any evidence for sexual dimorphism in our study may be that the sample sizes studied here were too small to reveal such a difference (a trend of males being longer than females was seen in TBL of the Israeli and Spanish, but not of the French sample group; data not shown).…”
Section: Sexual Dimorphismmentioning
confidence: 99%
“…Differences in primary productivity and subsequently resource availability could explain some of the body size variation in BDs on a worldwide scale. For example, the Gulf of Mexico with the adjoining Atlantic waters is an oligotrophic basin with primary production generally comparable with that of the Mediterranean (Pennock et al 1999), and BDs in this region generally do not exceed the size of their Mediterranean conspecifics (McFee et al 2010), while BDs in the eutrophic waters of the northwest Pacific or northeast Atlantic are remarkably large (Wells & Scott 2009). Thus, food resource availability can stand as a working hypothesis for BD nanism in the Levantine Basin.…”
Section: Environmental Factors and Levantine Nanismmentioning
confidence: 99%